Improvement of Integrated Sago Processing in Meranti Islands Regency - Agus Triputranto; Henky Henanto; Bambang Harianto; Mohammad Djali (Tropical Plantation Journal, 2023)
Sago plant (Metoxylon SP) for the community in the Regency of the Meranti Islands has an important role in the life and economy of its people. The prospect of developing the sago business in Meranti is still promising because   The land used has only reached 43% of the available land,  and management can still be optimized.  Sago processing that is currently operated is still running conventionally. That is, it only produces sago starch products. Its by-products in the form of waste from the pulp (repu) and skin (uyung) have not been optimally utilized. This study aims to optimize the processing of by-products into high-value products through improving sago management towards the concept of a zero waste industry in the Meranti Islands Regency, Riau Province. The results of the research that has been carried out show that it is necessary to add a process flow to the processing so that the resulting sago repu is not wet. The resulting dried sago repu will expand its utilization. From supporting studies, the results of studies  that have been carried out show that fermentation using  Trichoderma can increase protein by 18-22%. Using this Trichoderma mushroom, sago pulp can be used as animal feed or as raw material for biomass